Hubungan Pelayanan Service Excellent dengan Tingkatkepuasan Pasien Ibu Bersalin di PMB Pera Kota Medan - Ridesman Ridesman; Riska Susanti Pasaribu; Mediana Sembiring; Lasria Simamora; Nurmalina Hutahaean (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
The National Health System (SKN) states that the goal of health development is to achieve the ability to live healthily for every resident in order to realize an optimal level of health as one of the elements of general welfare, one of the efforts to achieve this goal is to carry out comprehensive, integrated and equitable health efforts that can be accepted and affordable by the entire community with the active role of the community, namely hospital referrals. Customer satisfaction can be increased by improving the quality of service, namely by using customer analysis including reliability, credibility, competence, tangible and responsiveness. This study aims to determine the Relationship between Service Excellent Midwifery Services and Patient Satisfaction of Maternity Mothers. The population in this study were all mothers giving birth at the Independent Practice of Midwives Pera. The number of samples in this study was taken by random sampling, totaling 63 people. The results obtained in this study from 63 respondents at the Independent Practice of Midwives Pera, Medan City in 2021 stated that service excellent Good towards Satisfaction of Maternity Mothers who were dissatisfied were 35 people (83%) and in service excellent Good towards satisfaction of satisfied mothers there were 7 people (17%). There is a Reability variable with good service with poor patient satisfaction of 34 people (83%) and good service with good patient satisfaction of 7 people (17%). There is a Credibility variable with good service with poor patient satisfaction of 18 people (53%) and good service with good patient satisfaction of 16 people (47%). There is a Competence variable with good service with poor patient satisfaction of 33 people (80%) and good service with good patient satisfaction of 8 people (19%). There is a Tangible variable with good service with poor patient satisfaction of 35 people (83%) and good service with good patient satisfaction of 7 people (17%). There is a Responsiveness variable with good service with poor patient satisfaction of 34 people (83%) and good service with good patient satisfaction of 7 people (17%).